Chitosan-PVA-co-poly (2-Acrylamido-2-Methylpropane Sulfonic Acid) Cross-linked Hybrid IPN-Nanogels for Transdermal Delivery of Ondansetron; Synthesis, Characterization and Toxicological Evaluation. Issue 17 (22nd November 2021) - Tanveer, Sana; Ahmad, Mahmood; Minhas, Muhammad Usman; Ahmad, Aousaf; Khan, Kifayat Ullah
ABSTRACT: Current study aimed to develop and evaluate interpenetrating polymer network (IPN) nanogels for transdermal delivery of ondansetron (OND) using combination of natural and synthetic polymers. Owing to their small size and biocompatible profile, nanogels have great potential as carriers for transdermal delivery that aids in penetration of drugs through layers of skin into blood stream. IPN nanogels were synthesized by free radical polymerization technique. Effective response for swelling and drug release were quantified at pH 5.5 and 7.4 simulating skin and blood. Overall results were satisfactory concluding that prepared IPN-nanogels were stable with excellent drug permeation profile across skin.